The Institute As A Counter-Institution - srpski (Sociološki pregled, 2020)
The Institute for Philosophy and Social Theory (hereinafter: the IPST) has presented to the public, both scientific and general, a book about itself: in which it named itself a counter-institution whose roots can be traced as far back as the Bled convention of 1960 and the reflection theory. The book in question is The Construction of a Counter-Institution: A History of the Institute of Philosophy and Social Theory, issued in September 2019. This publication, which will be distributed to libraries and thus bear witness to its time, presents the character of what is supposed to be a scientific institution. (As some associates have described it in their public speeches, “institutional insubordination” is the feature of the IPST). Three segments of this book are particularly engaging: 1) meaning of the counter-institution, 2) history of the IPST (or its history until 1960 and since then until present day), 3) role of Director of the Institute, Petar Bojanić, PhD.